Forest Ioggers plead 'not guilty' - Esteve, Jean (Technical Centre for Agricultural and Rural Cooperation, 1990)
Jean ESTEVE, he is a forestry scientist and consultant who has been with the Centre Technique Forestier Tropical (CTFT) for the past 25 years. CTFT is the forestry department of Centre de Cooperation Internationale en Recherche Agronomique pour le...